PENGARUH PENGGUNAAN MEDIA EDUKASI AUDIO VISUAL TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG GIZI DALAM KEHAMILAN - Renda Natalina Pratama (IKesT Muhammadiyah Palembang, 2023)
Readiness and alertness during pregnancy are needed, among others, to fulfill nutritional requirements during pregnancy. One of the efforts to improve the nutritional status of pregnant women is to increase the knowledge of mothers and families about the importance of nutritional adequacy. The purpose of this study was to determine how the effect of education using audio-visual media can increase the knowledge of pregnant women about nutrition in pregnancy. This research will be conducted using a quasi experimental design. Research subjects or respondents were given an intervention in the form of audiovisual media to increase knowledge about nutrition during pregnancy. Sampling in this study used an accidental sampling technique, where the respondents were 50 pregnant women who came at the time of data collection for approximately 4 months from February to June 2022. The results of the study were based on statistical analysis of the results of the calculation of the Wilcoxon Signed Rank Test, the Z value obtained was -6.044 with a p value (Asymp. Sig 2 tailed) of 0.000 which was less than the critical research limit of 0.05, there was a significant difference between the pretest group and the posttest. There was an increase in respondents' knowledge after being given health education using audio-visual media from an average pretest result of 74.76 and an average posttest result of 86.60. It is suggested that audio-visual media can be used to provide easier health education for the community because it has advantages in terms of providing good visualization so as to facilitate the absorption of knowledge.